PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF CHILDREN'S COLOR PERCEPTION AND THEIR IMPLEMENTATION IN WATERCOLOR PAINTING - Jennet Gurbannepesova (American Journals, 2025)
This article examines the characteristics of color perception in primary school-aged children, its psychological and pedagogical aspects, and the possibilities of implementing these characteristics in watercolor painting. It analyzes the patterns of color perception development, the role of color in shaping emotional and artistic perception, and reveals methodological techniques for using watercolors as a means of developing children's creative abilities.
Keywords: Color perception, watercolor painting, art education, psychological and pedagogical features, primary school age.